Effect of adding the sifting Avocado seed meals to wheat flour on produced characteristics of biscuits (Latakia University Journal -Biological Sciences Series, 2019)
Adding the sifting meals of the Avocado seed to wheat flour mixtures caused increasing in folowing percentages of components: (moisture , fibers , ash , starch and total soluble sugars ) Also the (5,10%) percentages adding caused a slight reducing in gluten quality , while a reducing in gluten quality was at (15 , 20 , 25%) percentages. Also the adding of tested meals caused reducing the sensory properties of produced biscuits , except the sensory properties of (5 ,10%) percentages , which improved significantly , comparing with control sample. Finally , Rheological properties of the( 5 and 10%) blended flour , show increase in thermal stability of amylases comparing with control sample , while other characteristics did,not effected clearly. أعطتْ إضافة المطحون المغربل من بذور الأفوكادو إلى خلطات دقيق القمح المُعدة لتصنيع البسكويت بالنسب المدروسة ، ارتفاعاً في محتواها من المكونات التالية: (رطوبة ، ألياف ، رماد ، نشا ، سكريات ذائبة كلية) وذلك بزيادة نسبة الخلط بهذا المطحون ، بينما انخفضت نسبة البروتين والحموضة . تراجعت نوعية الجلوتين في عينات الدقيق بعد العجن وذلك بشكل مقبول في الخلطتين (5 ، 10%) لتصبح هاتين الخلطتين الأنسب لتصنيع البسكويت لناحية قوة الجلوتين ، بينما كان التراجع أكثر وضوحاً في الخلطات (15 ، 20 ، 25%). تراجعتْ كذلك الصفات الحسية (المذاقية) لعينات البسكويت بزيادة نسبة مطحون بذور الأفوكادو في خلطات الدقيق ، باستثناء نسبة الخلط 5 ، 10% التي حصلت على أعلى درجات التقييم الحسي في كل الصفات المدروسة وجاءتْ متقاربة نسبيّاً مع عينات الشاهد . أظهر قياس الخواص الريولوجية بجهاز ميكسولاب لخلطات الشاهد و5% و10% مع دقيق القمح تحسّناً في الثبات الحراري للإنزيمات المحللة للنشا مقارنةً بالشاهد ، ولم تتأثّر باقي الخواص الأخرى بدرجة ملحوظة.